2017
DOI: 10.24820/ark.5550190.p010.185
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatization of 3,5-dinitropyridines – an atom-efficient approach to fused 3-nitropyrrolidines

Abstract: An efficient and convenient one-step method for the synthesis of decahydrodipyrrolo [3,4-b:3',4'-d]pyridine derivatives was developed on the basis of 1,3-dipolar cycloaddition of unstabilized N-methyl azomethine ylide with 2-substituted 3,5-dinitropyridines. This novel heterocyclic system contains two 3-nitropyrrolidine fragments fused to a partially saturated pyridine ring. Such types of compound, as follows from the literature, can be considered as potential nitric oxide donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…This allows to synthesize highly functionalized heteroaromatics combining several pharmacophoric moieties in the same molecule, interesting from the standpoint of design of novel pharmaceuticals. The work continues our ongoing project on the synthesis of complex hybrid molecules – furoxan-containing potential NO donors [ 19 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This allows to synthesize highly functionalized heteroaromatics combining several pharmacophoric moieties in the same molecule, interesting from the standpoint of design of novel pharmaceuticals. The work continues our ongoing project on the synthesis of complex hybrid molecules – furoxan-containing potential NO donors [ 19 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that this reaction resulted in the addition of two molecules of a dipole to the pyridine nucleus with the formation of compound 5. It is known that, in similar reactions, the addition of a dipole occurs from the opposite sides of the benzene (pyridine) ring, providing trans-cycloadducts [19,20,22,23]. However there are examples of the formation of cis-cycloadducts [24].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we reported on the development of a method for the synthesis of pyrrolidine and pyrroline derivatives condensed with a pyridine ring on the basis of 2-R-3,5-dinitropyridines [19,20]. It was shown that, depending on the nature of 2-R, annulation of either two pyrrolidine rings or one pyrroline ring is possible [20], Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, dearomatization as a method of converting accessible, cheap, and simple aromatic compounds into more saturated, inaccessible and promising intermediates of greater molecular complexity is a very important approach in modern organic chemistry [36,37]. This work is part of our ongoing research on highly electrophilic systems and the application of the dearomatization strategy in the synthesis of new polyfunctional azaheterocycles [38][39][40][41][42][43][44][45][46][47][48]. We have previously shown that nitropyridines fused with π-deficient heterocycles (furoxan A, selenadiazole B), Scheme 1, react with neutral nucleophiles with the formation of 1,4-addition productsdihydropyridine derivatives [45,46,48].…”
Section: Synthesis Of 6-r-isoxazolo[43-b]pyridines 3a-jmentioning
confidence: 99%